2015
DOI: 10.1016/j.visres.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Transformation priming helps to disambiguate sudden changes of sensory inputs

Abstract: Retinal input is riddled with abrupt transients due to self-motion, changes in illumination, object-motion, etc. Our visual system must correctly interpret each of these changes to keep visual perception consistent and sensitive. This poses an enormous challenge, as many transients are highly ambiguous in that they are consistent with many alternative physical transformations. Here we investigated inter-trial effects in three situations with sudden and ambiguous transients, each presenting two alternative appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The maximal induced destabilization was determined using the longest posttrigger interval duration (T post ¼ 320 ms; for further details, see the Results sections for Experiments 1 and 2). Please note that the effectiveness of the motion transient in inducing a perceptual reversal depends not only on its strength but also on a prior perceptual history (Pastukhov, Vivian-Griffiths, & Braun, 2015). The same procedure but using variable pretrigger intervals has been used to study the onset perception of SFM displays (Pastukhov, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The maximal induced destabilization was determined using the longest posttrigger interval duration (T post ¼ 320 ms; for further details, see the Results sections for Experiments 1 and 2). Please note that the effectiveness of the motion transient in inducing a perceptual reversal depends not only on its strength but also on a prior perceptual history (Pastukhov, Vivian-Griffiths, & Braun, 2015). The same procedure but using variable pretrigger intervals has been used to study the onset perception of SFM displays (Pastukhov, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Also, participants had a strong tendency towards interpreting the stimulus just as they did in the previous trial (Fig 2C). Such a perceptual stability over time is a classic finding in the study of ambiguous displays [13, 15, 21, 32], and it has recently been demonstrated also for the stream-bounce display [33]. This shows that perceptual disambiguation also relies on the combination of current sensory information with memory of recent perceptual interpretations [34, 35].…”
Section: Resultsmentioning
confidence: 87%
“…As an aside, the existence of distinctly different, complementary transition thresholds for bCFS and reCFS is reminiscent of the behavior termed hysteresis: a property of dynamical systems wherein output values, rather than being solely governed by corresponding input values, also exhibit lags or delays based on the valence of continuous changes in the input values. Examples of hysteresis in visual perception include transitions between binocular fusion and binocular rivalry ( Anderson, 1992 ; Buckthought et al, 2008 ; Julesz and Tyler, 1976 ), perception of motion direction in random-dot cinematograms ( Williams et al, 1986 ), and repetition priming in perception of bistable configurations ( Pastukhov et al, 2015 ). To paraphrase Maglio and Polman, 2016 , hysteresis can be construed as a form of memory whereby prior states influence the persistence of current states into the future.…”
Section: Discussionmentioning
confidence: 99%